2022
DOI: 10.3390/cells11182904
|View full text |Cite
|
Sign up to set email alerts
|

Gene Profiling of a 3D Psoriatic Skin Model Enriched in T Cells: Downregulation of PTPRM Promotes Keratinocyte Proliferation through Excessive ERK1/2 Signaling

Abstract: Psoriasis is a complex, immune-mediated skin disease involving a wide range of epithelial and immune cells. The underlying mechanisms that govern the epidermal defects and immunological dysfunction observed in this condition remain largely unknown. In recent years, the emergence of new, more sophisticated models has allowed the evolution of our knowledge of the pathogenesis of psoriasis. The development of psoriatic skin biomaterials that more closely mimic native psoriatic skin provides advanced preclinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…Each skin substitute was reconstructed according to the self-assembly method described previously elsewhere [ 27 ]. Fibroblasts at passage 5 were cultured over a period of 28 days in 6-well plates with a paper anchor, at a concentration of 1.2 × 10 4 cells/well.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each skin substitute was reconstructed according to the self-assembly method described previously elsewhere [ 27 ]. Fibroblasts at passage 5 were cultured over a period of 28 days in 6-well plates with a paper anchor, at a concentration of 1.2 × 10 4 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Ascorbic acid was added to the medium to form fully manipulable dermal sheets. Human T cells were then isolated from the blood extract of healthy donors and polarized and activated according to the protocol previously reported by our team [ 27 ]. Briefly, T cells were isolated by negative selection from whole blood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although substantial research has been carried out to clarify the pathophysiology of skin diseases, much remains to be discovered regarding the cellular mechanisms of cutaneous disorders. In this context, the editors of the journal Cells decided to create a Special Issue, entitled “Cellular Mechanisms of Skin Diseases.” It encompasses six articles covering various aspects of skin structure [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
mentioning
confidence: 99%
“…Brewer et al demonstrated that keratinocyte differentiation in tandem with an inflammatory milieu (IL-4/13) or barrier disruption (TJDP treatment) substantially changes the susceptibility to viral infection [ 2 ]. A possible cellular mechanism of human hypertrophic scars and keloids was highlighted by Petrou and colleagues [ 3 ], and a 3D psoriatic skin model enriched in T cells and its gene profiling was shown by Rioux et al [ 4 ]. Second, Nowicka and colleagues assessed various aspects of lymphomatoid papulosis (LyP) and mentioned that because of the expanded risk of lymphoma development, patients diagnosed with LyP need lifelong follow-up, and many of them will develop malignant neoplasms in the future [ 5 ].…”
mentioning
confidence: 99%